Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1097/shk.0000000000001833
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Levels of Matrix Metalloproteinase-3 and Tissue-Inhibitor of Matrix Metalloproteinases-1 Associate With Organ Dysfunction and Mortality in Sepsis

Abstract: Background: Matrix Metalloproteinases (MMP) respond to tissue damage during sepsis. Higher plasma concentrations of MMPs and the tissue-inhibitor of matrix metalloproteinases (TIMP) have been reported in sepsis compared with healthy controls. The objective of this study was to examine if plasma levels of MMP-3, MMP-9, and TIMP-1 associate with mortality and organ dysfunction during sepsis. Methods: We conducted a prospective cohort study of critically ill patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 59 publications
0
7
0
1
Order By: Relevance
“…In clinical cohorts, TIMP-1 systemic level was significantly higher in ARDS subjects than in other sub-groups of ventilated patients with respiratory failure, and it was independently associated with 90-day mortality and worse hypoxemia [28]. Likewise, higher plasma of TIMP-1 concentration was significantly associated with ARDS and 30-day mortality risk in critically ill patients admitted to the ICU [29]. These findings demonstrate the prognostic potential of circulating TIMP-1 in ARDS and encourage further biomarker studies to be conducted.…”
Section: Discussionmentioning
confidence: 95%
“…In clinical cohorts, TIMP-1 systemic level was significantly higher in ARDS subjects than in other sub-groups of ventilated patients with respiratory failure, and it was independently associated with 90-day mortality and worse hypoxemia [28]. Likewise, higher plasma of TIMP-1 concentration was significantly associated with ARDS and 30-day mortality risk in critically ill patients admitted to the ICU [29]. These findings demonstrate the prognostic potential of circulating TIMP-1 in ARDS and encourage further biomarker studies to be conducted.…”
Section: Discussionmentioning
confidence: 95%
“…The role of TIMP1 in sepsis has also been revealed. It is reported that compared with the healthy control group, the plasma concentration of TIMP1 in patients with sepsis is higher, which is a marker of acute renal injury and can be used to predict the prognosis [22] . It has also been reported that plasma TIMP1 concentration is associated with organ dysfunction in patients with sepsis [18] .…”
Section: Resultsmentioning
confidence: 99%
“…2 ). This observation might be related to MMP activity since it has been shown that higher plasma levels of MMP-3 are associated with septic shock and mortality 68 . C22, C39, C43 and C45 seem to play only a minor, if any, role during systemic inflammation because they were not detected or below the LLOQ in septic patients (Fig.…”
Section: Discussionmentioning
confidence: 97%